PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK MELALUI MODEL CLIS (CHILDREN LEARNING IN SCIENCE) KELAS IV SD NEGERI 179 PALEMBANG - Tiurida Intika (LP4MK STKIP PGRI Lubuklinggau, 2019)
The objective of research was to improve students' learning outcome on thematic learning through CLIS model (Children Learning In Science) in the fourth class of elementary school number 179 Palembang. The design of the research was action research. The subject of the research was 27 students of IVC including 13 male students and 14 female students. Technique of data analysis used test, observation and documentation. Based on the research result, it was proved that the average score in pre-cycle was 62 with learning mastery 30.8% (fair), the average score in cycle I increased 70.9 with learning mastery 44.4% (enough). While the average score in cycle II also increased 75.2 with learning mastery 85.1% (very good). The average percentage of students' participation also increased from cycle I (61.9%) in enough active category to cycle II (71.1%) in active category. In summary, CLIS model (Children Learning In Science) can improve students' learning outcome. Therefore, the researcher suggests that the teachers apply CLIS model in the teaching and learning process.